Description Of Growth Of Devotion In Public Health Tanete Bulukumba District - Andi Nurlaily; Kurniati, Ely (Jurnal Life Birth, 2017)
Very rapid growth and development occur at the age of five, known as the golden age phase, therefore this phase is a very important period in terms of growth and development. The purpose of this study was to determine "Overview of Toddler Growth and Development in Tanete Health Center in Bulukumba Regency in 2016". This type of research is descriptive research with a cross-sectional approach. The sample in this study was 75 toddlers with a total population of 343 toddlers with regard to growth and development. From table 4.1 shows that most respondents were toddlers with an age of 1 year, amounting to 21 people (28%), and the least respondents were toddlers aged 5 years which numbered 9 people (12%). The distribution of respondents with the highest sex was toddlers with male sex, amounting to 40 people (53.3%). From table 4.2 shows that the distribution of respondents with normal body weight is 44 people (58.6%). The distribution of respondents with normal height was 46 people (61.3%). Distribution of respondents with a normal head circumference of 66 people (88%). From table 4.3 shows that the distribution of respondents with normal gross motor skills was 54 people (72%). Distribution of respondents with normal motor numbered 42 people (56%) Conclusion of the data, the results of the study showed that the highest distribution of respondents was toddlers with normal growth. The results obtained by the distribution of most respondents are with normal development. It is hoped that the results of this study can be used as a material for consideration and reference in the effort to detect early childhood growth and development.